Burkeite and hanksite at Copahue, Argentina: The first occurrence of sulphate-carbonate minerals in a geothermal field - Mas, Graciela Raquel (2007)
Deposition of two anhydrous sulphate-carbonate minerals, burkeite and hanksite, around a vapour escape in the pipe of a geothermal well of the Copahue field in Argentina is described. These minerals usually occur as efflorescences in saline soils or in continental lacustrine evaporite deposits, but have not been reported as products from geothermal fluids. Both minerals have been studied by means of X-ray diffraction, scanning electron microscopy and electron dispersive energy, and thermo-gravimetric analysis, and have been determined as burkeite, Na6(CO3)(SO4)2, and hanksite, KNa22(SO4)9 (CO3)2Cl.